Lohnentwicklung im Lebenszyklus - Eine Analyse von Ausmaß, Begründung und Heterogenität von Lohnsteigerungen - Orlowski, Robert; Riphahn, Regina Therese (Journal for labour market research, 2011)
Der Beitrag fasst die Ergebnisse einer Reihe von Untersuchungen zusammen, die sich auf Basis der Daten des deutschen Sozio-oekonomischen Panels (SOEP) mit der Lohnstruktur auf deutschen Arbeitsmärkten beschäftigen. Die Analysen nutzen neben Kleinstquadrateschätzern die von Altonji und Shakotko, Rev. Econ. Stud. 54, 437 (1987) und von Topel, J. Polit Econ. 99(1), 145 (1991) verwendeten Schätzverfahren. Diese berücksichtigen die Endogenität der Indikatoren von firmenspezifischer und allgemeiner Arbeitsmarkterfahrung. Der Fokus des Beitrages liegt auf der Analyse möglicher Heterogenitäten in den Lohnstrukturen im privaten und im öffentlichen Sektor, in Ost- und in Westdeutschland, für Männer und Frauen sowie bei Arbeitgebern in großen und kleinen Unternehmen. Die interessantesten Ergebnisse heben deutliche Unterschiede zwischen Ost und West sowie zwischen großen und kleinen Unternehmen hervo
WiSo-Import:2015-03-26:883
Keywords: Transformation; Lohnstruktur; Humankapital; Firmenzugehörigkeitsdauer

Seniority in Germany: New Evidence on Returns to Tenure for Male Full-time Workers - Riphahn, Regina Therese; Orlowski, Robert (Journal for labour market research, 2008)
This study uses recent data taken from the German Socioeconomic Panel (2002-2006) to evaluate the extent of and heterogeneity in returns to tenure for men in East and West Germany, employed in both the private and the public sector. We find significantly different wage patterns in East- and West Germany as well as between the private and public sector. Independent of the particular subsample, the application of the Altonji-Shakotko estimation approach yields minute and insignificant returns to tenure and more substantial returns to experience. The profile of the East German wage structure is surprisingly flat: after the first ten years of experience - and in contrast to the situation in West Germany - there appear to be no returns to additional general human capita
WiSo-Import:2015-03-26:1037
Keywords: Transformation; seniority; returns to tenure; private and public sector; earnings patterns

The East German wage structure after transition - Orlowski, Robert; Riphahn, Regina Therese (Economics of Transition, 2009)
We extend the literature on transition economies’ wage structures by investigating the returns to tenure and experience. This study applies recent panel data and estimation approaches that control for hitherto neglected biases. We compare the life-cycle structure of East and West German wages for fulltime employed men in the private sector. The patterns in the returns to seniority are similar for the two regional labour markets. The returns to experience lag behind in the East German labour market, even almost 20 years after unification, with significant differences particularly for high-skill workers. The results are robust when only individuals who started their labour market career in the market economy are considered. We expect that the different returns are related to the heterogeneity of work experience gathered in East as compared with West German
WiSo-Import:2015-03-25:308
Keywords: Transformation